The effects of giving “kecek”grasshopper(Orthoptera)stimulatorfrequencies of3000 Hz on teak (Tectona grandis)seeding and peanut(Arachis hypogeae, L) planting - Anissa Yusi A’mallina; Juli Astono (Jurnal Sains Dasar, 2014)
The purpose of this research is to know the effects of giving “kecek”grasshopper(Orthoptera)frequencies of 3000Hz in teak (Tectona grandis) seedingand peanut (Arachis hypogeae, L) plantingtowards the growth, wide openingof stomata, and plant productivity. The sound that used in this research is sound of “kecek”grasshopper(Orthoptera) with peak frequencies of the original sound is (4.3 ± 0.6) 103Hz and peak frequencies ofthe manipulated sound is(3,010 ± 14) Hz. Objects of this research areteak (Tectona grandis) seeds and peanuts(Arachis hypogeae, L). The resultsof thisresearch include: plant height, stem diameter, leaf length, leaf width,number of leaf, and yield of mass analyze using Microsoft Excel and Microsoft Origin 6.1, while to determinetheopening width of stomataOptilab Image Raster program was used.The results showed that the growth,productivity, and stomata width aperture of treatment plants arebetter than the control plants.Keywords: sound of “kecek”grasshopper(Orthoptera), teak (Tectona grandis), peanut (Arachis hypogeae, L),stimulator frequencies